2012
DOI: 10.1590/s0100-879x2011007500158
|View full text |Cite
|
Sign up to set email alerts
|

Serum metabolic profiling of human gastric cancer based on gas chromatography/mass spectrometry

Abstract: Research on molecular mechanisms of carcinogenesis plays an important role in diagnosing and treating gastric cancer. Metabolic profiling may offer the opportunity to understand the molecular mechanism of carcinogenesis and help to non-invasively identify the potential biomarkers for the early diagnosis of human gastric cancer. The aims of this study were to explore the underlying metabolic mechanisms of gastric cancer and to identify biomarkers associated with morbidity. Gas chromatography/mass spectrometry (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 32 publications
2
39
0
Order By: Relevance
“…Miyagi et al observed that citrulline, valine, tryptophan and histidine levels were significantly lower in GC patient plasma, whereas isoleucine and lysine were higher . Song et al demonstrated that plasma glutamine level decreased in GC patients . Our study generated similar results that GC patients had lower glutamine, histidine, arginine and tryptophan levels and higher ornithine concentration.…”
Section: Discussionsupporting
confidence: 84%
“…Miyagi et al observed that citrulline, valine, tryptophan and histidine levels were significantly lower in GC patient plasma, whereas isoleucine and lysine were higher . Song et al demonstrated that plasma glutamine level decreased in GC patients . Our study generated similar results that GC patients had lower glutamine, histidine, arginine and tryptophan levels and higher ornithine concentration.…”
Section: Discussionsupporting
confidence: 84%
“…Nine studies investigated esophageal cancer (39-47), 3 gastric cancer (48)(49)(50), and 15 colorectal cancer (29,30,(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). Two studies investigated more than one GI malignancy (64,65).…”
Section: Resultsmentioning
confidence: 99%
“…Measuring the serum level of tumor markers (VEGF, IL-6), oxidative stress markers (Nitric oxide, MDA) [20], gastric mucosal secretary markers (Gastrin-17, Pepsinogen I [21], and Eicosanoids (prostaglandins, leukotriene) [22] are among these studies. Profiling metabolites in the serum and urine of gastric cancer patients revealed a total of 18 and 7 biomolecules (including carbohydrates, amino acids, fatty acids, and steroids) with a significant difference in comparison with the serum and urine of normal individuals, respectively [23][24][25]. Among these metabolic fingerprints, amino acids take a particular part.…”
Section: Discussionmentioning
confidence: 99%
“…Among these metabolic fingerprints, amino acids take a particular part. While the serum levels of glutamine is depleted due to increased consumption of this metabolite, the serum level of valin is increased due to possible increase in valin catabolism by cancer cells [23]. On the other hand, there is a significant decline in the urinary level of L-serin and L-threonin due to participation of these two amines in glycolysis or Tri carboxylic acid (TCA) cycle [25].…”
Section: Discussionmentioning
confidence: 99%